(untitled) (Academicia Globe: Inderscience Research, 2025)
This paper discusses the scientific research related to the evaluation of the impact of the activities of Mamun University on the economy of the region is reflected. According to the results of the research, the total number of students studying at the university (both full-time and part-time courses), the total income of the university, the total number of professors, teachers, supervisors and workers who are employed at the university were found to have a positive effect on the GNP of the region. Also, in the research work, the results of forecasting the total number of university students for the next three-year period were developed. In addition future prospects of the university have been explained and strategies that will play important role in the development of both university and the region’s economy have been developed and discussed.